2006 Fonda Cordobesa - Grupo Teatro La Cochera (2017)
Idea: Paco Giménez | Actúan: ALicia Alvarado, Marcelo Castillo, Gabriela duran, Alejandra Garabano, Veky Araceli Gómez, Guillermo Wright | Dirección: Paco Giménez | Consultado el 5 de octubre de 2016 | http://www.alternativateatral.com/obra13283-la-fonda-cordobesa